METHODS AND TECHNIQUES USED DURING THE DEVELOPING COMMUNICATIVE SKILLS (American Journal of Research in Humanities and Social Sciences, 2023)
The article presents studies on the implementation ways of communicative language teaching activities in the classroom. The article is given the topicality, aim, and practical significance of the chosen theme. It is fully proved the importance of communicative language teaching activities in teaching language. The actuality of this work is the investigation of some innovative communicative language teaching activities in the way of development of speaking skills to provide communication in learning a foreign language and making ESP classrooms more effective teaching environments as a facilitator.